Synthesis and Characterization of Nano-crystalline ZSM-5 Zeolite - Majeed, Najwa Saber; Alnaama, Asir Abduljabbar (Al-Khwarizmi Engineering Journal, 2015)
Abstract Nano-crystalline ZSM-5 zeolite was synthesized by hydrothermal method using chelating agent and two gel compositions:Compositionɪ:Al2O3:86SiO2:5.5TPA:12.7Na2O:3.4Trien:3320H2O.Compositionɪɪ:Al2O3:68SiO2:5.4TPA:10Na2O:2.6Trien:2626H2O.Study of hydrothermal reaction factors on characteristics of nano- sized zsm-5 has been carried on ,among them are crystallization temperature, crystallization time and concentration of template ( TPAOH ) solution. Synthesis was accomplished in PTFE lined autoclave ( reactor ) . The product were characterized by X-ray diffraction ( XRD ),Atomic force microscopy ( AFM ),scanning electron microscopy, Fourier transform infrared ( FTIR ) and Brunauer-Emmet-Teller (N2 absorption-desorption isotherm).SEM and XRD results indicate that crystallinity of synthesized zeolite increase with increasing crystallization time and temperature. AFM results indicate that a nano-sized level of about 50nm was reached for "particle average diameter". FTIR results showed that the required peaks near "1080,800,550,450 cm-1" have been clearly obtained, Furthermore the results showed strong effect of template (TPAOH) solution concentration on crystallinity and decreasing of particle size towards nano-size level.  Keywords: Crystallization , Template, Synthesis, Nanocrystalline, ZSM-5 zeolite.